2017
DOI: 10.4236/ojneph.2017.72004
|View full text |Cite
|
Sign up to set email alerts
|

Anxio-Depressive Morbidity in Chronic Hemodialysis at the CHU SO of Lome (Togo)

Abstract: Introduction: This work aims to identify and analyze the anxio-depressive morbidity that the renal insufficiency in hemodialysis can present. Methodology: The framework of this work was the department of nephrology and the hemodialysis unit of the CHU Sylvanus Olympio of Lome. This was a crosssectional, single-pass, descriptive and analytical study that ran from January 1 st , 2016 to June 30 th , 2016. Included were all chronic hemodialysis patients who gave their free and well-informed consent and who have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The level of overt and hidden anxiety among the evaluated hemodialysis patients was moderate to high. In this regard, Soedje et al showed that anxiety among hemodialysis patients was very high due to poor access to dialysis treatment centers and increased treatment duration, consistent with the present research findings (31). El Filali et al reported the presence of anxiety in dialysis patients and its effect on the loss of quality of life in the moderate range, which is consistent with the results of the present study (32).…”
Section: Discussionsupporting
confidence: 92%
“…The level of overt and hidden anxiety among the evaluated hemodialysis patients was moderate to high. In this regard, Soedje et al showed that anxiety among hemodialysis patients was very high due to poor access to dialysis treatment centers and increased treatment duration, consistent with the present research findings (31). El Filali et al reported the presence of anxiety in dialysis patients and its effect on the loss of quality of life in the moderate range, which is consistent with the results of the present study (32).…”
Section: Discussionsupporting
confidence: 92%